School evaluation before and during the pandemic: how students see this moment (Research, Society and Development, 2021)
The purpose of this qualitative quali research is to present and discuss how students from a state school located in Minas Gerais see the school evaluation processes, their feelings about the subject, what types of evaluation they did most during their life, and how it affected them. It also shows how the COVID-19 pandemic affected school relationships and how were harming the students at that time. Even with all the obstacles faced due to the pandemic, this research was only possible using Information and Communication Technologies (ICTs). And in this work, a message exchange platform called WhatsApp was used to talk and provide information to the participants also, a questionnaire was answered by the students through the Google Forms platform. The results showed the students' fears and anxieties, their necessity and the importance they give to school evaluations. It shows the importance of the teacher and family in studies during remote education, as support was important at the time. The results show the future challenges of school life and how we can, from the student's perspective, perceive the demands of the new generation.